Sistem Penilaian Inovasi Karyawan Digital Amoeba Menggunakan Desain Arsitektur Microservice Pada Aplikasi Mobile - Fitran Dwi Pramakrisna; Faisal Dharma Adhinata; Nia Annisa Ferani Tanjung (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Digital Amoeba employees want an application system that can be integrated directly into the Ideabox application to be assessed the innoavtions directly. Therefore, innovations do not need to be assessed using third parties such as Google Sheets SurveyMonkey. Therefore, an application system called Scoring was created. This application system is designed using a microservice architecture design, where each service has its own database. The services used in the Scoring application system are User Service, Ideas Service, Event Service, and Scoring Service. The application system is built using the PHP programming language and the CodeIgniter version 4 framework. This system is implemented both on web and mobile platform